How Much Does Others' Protection Matter? Employment Protection, Future Labour Market Prospects and Well-Being - Christine Lücke; Andreas Knabe (Center for Economic Studies and ifo Institute (CESifo), 2018)
Employment protection legislation (EPL) is an important determinant of workers' perceived future labour market prospects as well as their subjective well-being. Recent studies indicate that it is not only a worker's own level of protection, but also the employment protection of other workers that matters for individual prospects and well-being. We contribute to this literature by examining how such cross-effects on well-being are mediated by a workers' perceived risk of job loss and future employability. We apply a structural model to data from the Third Wave of the European Quality of Life Survey, combined with summary indices from the OECD Employment Protection Database. Our results are indicative of cross-effects. Stricter protection for permanent workers (stricter regulation on the length and number of renewals of fixed-term contracts) is associated with lower (higher) perceived employability for both permanent workers and fixed-term workers. In addition, stricter protection for permanent workers is positively related to fixed-term workers' perceived risk of job loss. We do find some evidence that EPL has significant indirect (cross-)effects on life satisfaction via the mediators. There are no indications for direct, non-mediated effects.
Keywords: J28; J68; 330; employment protection; employability; risk of job loss; life satisfaction